2014
DOI: 10.1556/aalim.43.2014.suppl.25
|View full text |Cite
|
Sign up to set email alerts
|

Food additives and consumer preferences: A cross-cultural choice based conjoint analysis

Abstract: Important differences have been reported in several countries about the level of concern in connection with food additives. In order to better understand the consumer preferences related to foodstuffs containing food additives, fi ve hypotheses were tested with the help of a choice-based conjoint analysis. The study was performed in three European countries (Hungary, Romania, and Spain) having different risk perceptions concerning food additives. Two "model foodstuffs" were involved in the analysis: pre-packed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This is a very interesting result because handling citrus fruit with leaf presence implies a significant additional cost for the citrus industry. As the decision choice of food products can be affected by nationality [ 19 , 20 , 21 ], our finding opens the door to new studies with a view to elucidate whether this pattern is also true for other international markets.…”
Section: Discussionmentioning
confidence: 84%
“…This is a very interesting result because handling citrus fruit with leaf presence implies a significant additional cost for the citrus industry. As the decision choice of food products can be affected by nationality [ 19 , 20 , 21 ], our finding opens the door to new studies with a view to elucidate whether this pattern is also true for other international markets.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, Grunert et al (2015) and Topcu (2015) reported that these credence quality attributes were mainly focused on the extrinsic quality attributes of food products but not on the intrinsic ones, and often there were no relevant cues available. Szűcs et al (2014) suggested that consumer-led product design should incorporate the emerging credence quality attributes. Chamorro et al (2015), Almli et al (2015), Munoz et al (2015), and Topcu (2015) indicated that the most important information cues that consumers wanted to see on the label were related to the region of origin, brand, price, convenience, and the packaging material of the food products.…”
Section: Erzurummentioning
confidence: 99%
“…Some antimicrobials such as lysozyme, natamycin, chitosan, and nisin are also used to inhibit the microbial growth in specific types of cheese (Jalilzadeh et al., 2015). However, in general, consumers are skeptical of the use of food additives in terms of their safety (Szűcs et al., 2014).…”
Section: Introductionmentioning
confidence: 99%